The career maturity of the gifted and talented pupil - Rainier, Markseller Garrett (Rhodes University, Faculty of Education, Department of Education, 1984)
In 1980 the cape Education Department launched a Gifted and Talented programme in some schools which was intended to enrich the educational experience of the more able pupils. Numerous studies have shown these pupils to have a higher level of career maturity than non-gifted pupils, but the studies have also shown that these pupils face unique career- development problems. Gifted and Talented pupils constitute an important source of manpower and their potential contribution to the total society is great. Consequently they are in need of effective career guidance to help them overcome their unique problems and realize their potential. This study set out to discover if the career maturity of a group of Standard 9 Gifted and Talented pupils, identified according to the original Cape Education Department criteria, is indeed higher than that of their peers and to make recommendations for facilitating career education among these pupils. Contrary to expectations the Gifted and Talented pupils did not show significantly higher levels of career maturity than their peers, as measured on the Attitude Scale of Crites ' Career Maturity Inventory. Compared with the American norms , the scores obtained by the research population were unfavourable. The validity of the I .Q. scores used and the criteria for identification of Gifted and Talented pupils are seen as questionable which could have led to an inaccurate grouping of the pupils as Gifted and Talented or non- gifted. Recommendations are made for a basic career education programme for all pupils which would include periods of active work experience. Recommendations for additional career education for those currently classified as Gifted and Talented pupils are also made, so as to allow these pupils additional time for self- development, decisionmaking and dealing with their unique life situation
Keywords: Gifted children--Psychology; Counseling in vocational education